KONTRIBUSI MOTIVASI DAN PENGAWASAN ORANG TUA TERHADAP PRESTASI BELAJAR BAHASA INDONESIA PADA MASA ENDEMI - Hijriyah Hijriyah; Made Sri Indriani; Kadek Wirahyuni (Jurnal IKA, 2022)
The research conducted by the researcher aims to determine the effect of the motivation and supervision of parents together on learning achievement of Indonesian class XII MIPA 2 at MAN Buleleng during the endemic period. This research was motivated by the results of the researchers' observations when doing PPL-Adaptif in class XII MIPA 2 MAN Buleleng. Researchers found low student learning activities which were indicated by the presence of students who were less active when participating in Indonesian language learning, but when the teacher gave appreciation in the form of adding an active score to some students who were active in learning, other students were actively involved in further learning. Researchers suspect that there are motivational factors that affect student achievement. In addition, parents also play an important role in supervising, guiding, and providing direction for student learning activities carried out at home. This research is a quantitative-qualitative descriptive study. Data collection techniques used observation, questionnaires, interviews, and documentation with data instruments in the form of observation sheets, questionnaires, while data analysis used multiple linear analysis tests. Multiple linear analysis test produces a constant value (a) of 69,174, X1 coefficient of 0.295, X2 coefficient of 0.373. The percentage contribution of the influence of the motivational variables and parental supervision together on the achievement of learning Indonesian is 69.9%. In the multiple regression test, the significance value of 0,000 is smaller than 0,05 so that it can be concluded that the motivation and supervision of parents together affect the achievement of learning Indonesian in class XII MIPA 2 at MAN Buleleng.